2021
DOI: 10.1016/j.ijmedinf.2020.104309
|View full text |Cite
|
Sign up to set email alerts
|

Track Iran's national COVID-19 response committee’s major concerns using two-stage unsupervised topic modeling

Abstract: Background Since the World Health Organization (WHO) declared the COVID-19 as a Public Health Emergency of International Concern (PHEIC) on January 31, 2020, governments have been enfaced with crisis for timely responses. The efficacy of these responses directly depends on the social behaviors of the target society. People react to these actions with respect to the information they received from different channels, such as news and social networks. Thus, analyzing news demonstrates a brief view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…to explore similarities and differences of pandemic-related social-media discourse. Kaveh–Yazdy and Zarifzadeh [ 13 ] found that the main concerns of the Iranian public included topics related to “PCR lab, test, diagnosis, and screening”, “closure of the education system”, and “awareness actions about washing hands and facial mask usage”, based on the latent Dirichlet allocation (LDA) topic modeling results of 2,400,000 posts from official news channels. Liu et al [ 14 ] conducted another LDA topic model to analyze 7791 Chinese news articles about COVID-19 and discovered that prevention, control procedures, medical treatments, research, and global or local social and economic influences were the key themes.…”
Section: Literature Review and Theoretical Elaborationmentioning
confidence: 99%
“…to explore similarities and differences of pandemic-related social-media discourse. Kaveh–Yazdy and Zarifzadeh [ 13 ] found that the main concerns of the Iranian public included topics related to “PCR lab, test, diagnosis, and screening”, “closure of the education system”, and “awareness actions about washing hands and facial mask usage”, based on the latent Dirichlet allocation (LDA) topic modeling results of 2,400,000 posts from official news channels. Liu et al [ 14 ] conducted another LDA topic model to analyze 7791 Chinese news articles about COVID-19 and discovered that prevention, control procedures, medical treatments, research, and global or local social and economic influences were the key themes.…”
Section: Literature Review and Theoretical Elaborationmentioning
confidence: 99%
“…HaCohen-Kerner et al [45] investigations showed that bag-of-word text classification methods could be significantly benefitted from stop-word removal. Moreover, results of Kaveh-Yazdy et al studies [46], [47] showed that removing most frequent words (that are appeared in more than 𝑝 % of documents) as well as stop-word removal in Persian news mining applications produce better results. Therefore, most frequent words (words that appeared in more than 60% of articles) and stop-words are removed before vectorization.…”
Section: Baseline Uncertainty Index Constructionmentioning
confidence: 99%
“…Yang et al [ 29 ] comparatively analyzed textual news media data and found that the China Daily newspaper paid more attention to mask-wearing throughout the study period than its counterparts from the United Kingdom and the United States. Moreover, multiple studies in this category analyzed news media contents from Iran [ 30 ], Brazil [ 31 ], and Italy [ 32 ]. Face masks appeared in these studies only as a subtopic under the broad topic of prevention and control measures, indicating a lack of media focus.…”
Section: Introductionmentioning
confidence: 99%